Risk Preferences and the Adoption of Subsidised Crop Insurance: Evidence from Lithuania - Birgit Gassler; Regina Rehermann (German Journal of Agricultural Economics (GJAE), 2022)
Crop insurance adoption remains low among small and medium farms - despite financial public support in the form of premium subsidies. A better understanding of smaller farmers' insurance decisions and contract attribute preferences is thus needed to encourage insurance solutions. Moreover, previous research has primarily examined risk preferences and insurance adoption among Western European farmers, while little is known about insurance markets and risk preferences in Central and Eastern European countries. We contribute to the literature by i) contrasting the current status of insurance adoption by Lithuanian farmers by farm size, ii) assessing farmers' risk preferences and attitudes towards crop insurance, and iii) investigating small and medium farmers' preferences for the characteristics of a new (hypothetical) subsidised multiple peril crop insurance (MPCI) product. Therefore, we conduct a socio-economic survey in Lithuania that features a risk preference elicitation task and a discrete choice experiment (DCE). Findings show that, on average, sampled farmers are risk-neutral to slightly risk-seeking and that insurance adoption is lowest among smaller farms (50 hectares). Moreover, insurance adoption was associated with higher risk exposure, higher trust in insurance services, and higher willingness to take farming-specific risks on all farms. For small and medium farms, the DCE results suggest preference heterogeneity for contract attributes and higher adoption rates when contract design reduces the risks and efforts associated with subsidised insurance.
Keywords: 330; multiple peril crop insurance; small farms; Europeanagriculture; contract attribute preferences; discretechoice experiment